A fast and low-cost interface modification method to achieve high-performance garnet-based solid-state lithium metal batteries. (January 2022) - Zhao, Bing; Ma, Wencheng; Li, Bobo; Hu, Xiongtao; Lu, Shangying; Liu, Xiaoyu; Jiang, Yong; Zhang, Jiujun
Abstract: Garnet-based solid-state lithium metal batteries (SSLMBs) are considered to be the candidate power sources for electric vehicles and large-scale energy storage systems due to their high energy density, wide operating temperature and high safety. However, poor wettability of garnet/Li metal anode interface, large interfacial impedance and penetrating lithium dendrite growth during cycling limit the practical application of SSLMBs. In this paper, SnS2 ultra-thin film is fabricated on the surface of solid-state Li6.75 La3 Zr1.75 Ta0.25 O12 (LLZTO) electrolyte by a rapid (ca. 5 min) liquid-phase deposition method. Then, a Li2 S/Li x Sn mixed ionic/electronic conductive layer is in-situ constructed through the conversion reaction between molten Li and SnS2 . This mixed conductive layer can significantly reduce interfacial impedance, ensure intimate contact at the Li/garnet interface and inhibit growth of lithium dendrites. Thus, the resulting Li symmetric cell with Li2 S/Li x Sn modification layer exhibits a low interface resistance of 47 Ω cm 2 and a long lifespan over 1000 cycles. Moreover, using this Li/garnet interface, the full cell assembled with LiFePO4 cathode shows both excellent cycling and rate performance. These results demonstrate the feasibility of the proposed modification strategy for solid-state garnet electrolyte, and pave the way for the development of high-performance solid-state batteries. Graphical Abstract: A mixed ionic/electronic conductive Li2 S/Li x Sn layer is in-situ constructed through the conversion reaction between molten Li and SnS2 . Li2 S has a wide band gap which can prevent electron attack on LLZTO electrolyte. The Li x Sn alloy not only guides a homogeneous electronic distribution but also serves as a lithiophilic material to make an intimate LLZTO/Li contact at the interface. ga1 Highlights: SnS2 nanosheets are coated on LLZTO surface via a fast liquid deposition for interficial modification. A mixed ionic/electronic conductive Li2 S/Li x Sn layer is in-situ formed at LLZTO/Li interface. The Li2 S/Li x Sn layer improves wettability, decreases interfacial activation energy and prevents the electron attacking LLZTO. Li2 S/Li x Sn modified Li symmetric cell cycles stably over 1000 h at 0.2 mA cm −2 .